Early life acute infections and risk for cow's milk protein allergy or atopic dermatitis at 6 months of age in high risk for allergy infants - Pancheva, Rouzha; Illiodromiti, Zoi; Moschonis, George; Kontopodi, Eva; Karapati, Eleni; Nicolaou, Nicolaos; Karaglani, Eva; Sekkidou, Mikaela; Popova, Simoneta; Usheva, Nataliya; Marinova, Miglena; Xepapadaki, Paraskevi; et al. (Frontiers in Pediatrics, 2024)
BackgroundEarly life infections (ELIs), encompassing both viral and bacterial types, occur within the first six months of life. Influenced by genetic host factors and environmental conditions, the relationship between ELIs and subsequent allergic manifestations, particularly cow's milk protein allergy (CMPA) and atopic dermatitis (AD), is complex and not fully understood.ObjectiveThe aim of the current study was to examine the potential interplay between nutrition, infections, and allergic manifestations in the first six months of life in infants with a family history of allergies, who were either exclusively breastfed (EBF) or fed a combination of breast milk and standard (SF) or partially hydrolyzed infant formula (pHF).MethodsThe Allergy Reduction Trial (ART) is a multicenter, randomized controlled trial involving 551 participants. From birth, these participants were divided into three groups: Exclusive Breastfeeding (EBF), Partially Hydrolyzed Formula (pHF), and Standard Formula (SF). ELIs, defined as viral and bacterial infections occurring during the first 6 months, and outcomes (AD, CMPA) were recorded through questionnaires (i.e., SCORAD and CоMiSS) and clinical assessments.ResultsThe relative risk (RR) for CMPA in infants with ELIs was 0.20 (95% CI: 0.07–0.58), highlighting a protective effect of ELIs against CMPA development. Notably, the incidence of CMPA was significantly lower in infants who experienced ELIs compared to those without (3% vs. 13.4%, p = 0.001), with no cases of CMPA observed at 6 months in exclusively breastfed (EBF) infants with ELIs. For AD, a trend was observed where the incidence was lower in infants with ELIs who were fed with pHF at 6.5%, compared to those fed with SF at 18.2% (p = 0.092), suggesting a potential protective effect of ELIs in the pHF group against AD development.ConclusionThe study highlights a potential protective role of ELIs in reducing the risk of CMPA, particularly in EBF infants. Furthermore, it suggests a trend towards lower AD incidence in infants fed with pHF, highlighting the complex interplay between early microbial exposures, feeding practices, and immune development. Further research is warranted to unravel this challenging relationship and appropriately inform early life allergy prevention strategies